(3GdUMGFas - (3EHQGgje Hf CMeO GdeOYh HLGhT RGOg,J (B1053 (3g` s
(3ChdgG (B:s
(3Gddg CMeO Ydi Cf habfi dGeJKGd GdCeQ GdeWGY hjSQ di GdCJHGY ddoMde GdhGLH GdEJHGY s
(3BNQgG (B:s
(3GdKfGA GdLejd aPQjYJg GdKhGH GdLRjd HeMeO Udi Gddg Ydjg hYdi JGHYjg CLeYjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1075s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQGFV Mdje (B18) s
Keywords: (3Yde GdaQGFVs